Le point sur les travaux réalisés en amélioration des plantes sur les luzernes annuelles par le Programme Fourrages de l'Institut National de la Recherche Agronomique du Maroc - Bounejmate M. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
In the early 80's there has been increasing interest in the introduction of the Australian ley-farming system in Morocco. During the last fifteen years, the main part of our research program aimed to get a better knowledge of annual Medicago species in order to propose use of annual legume pastures in place of fallow. Local medic species and ecotypes have proven to be far adapted to local conditions than introduced cultivars. One thousand, eight hundred and fifty-five ecotypes belonging to 11 species were collected from 1983 to 1989 through six collections covering the main agronomic areas of the country. These accessions were studied in order to precise their distribution and environmental adaptation to pH, clay, phosphorus, nitrogen concentrations, temperature and rainfall. In parallel, agronomic experiments gave us satisfying information concerning dry matter and seed production. Five of these species were also compared for their coumestrol concentration as factor of fertility for ewes. At least the author insist on the importance of genetic erosion and the interest to survey and protect the rarer species.
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)